The composite aortic wall graft technique: an option for a short coronary artery bypass graft - Oliveira, João Bosco de (2009)
SUMMARY: During coronary artery bypass graft (CABG) surgery, the saphenous vein is sutured through its proximal segment to the aorta. Intimal hyperplasia is one of the possible causes of graft occlusion. Notably, blood turbulence can induce wall shear stress that may also play an important role in this process. OBJECTIVE: We propose a new technique for performing proximal anastomosis to avoid CABG failure. METHOD: An 80 kg pig was subjected to open heart surgery. Four stitches were placed in the anterior ascending aorta, which formed a 2 cm by 4 cm patch. This patch was isolated through the application of a tangential clamp that was oriented parallel to the axis of the aorta. After releasing the patch, which was held to the aorta through its cranial end pedicle, the rims were sutured to each other creating a conduit with a length of 4 cm and an internal diameter of 4 mm. The rest of the aortotomy was closed by placing a direct suture between its rims. RESULT: This novel technique created an "in situ" aortic wall graft that was 4 cm long and characterized as being of uniform 4 mm caliber.